Embedding of Ti3C2Tx Nanocrystals in MAPbI3 Microwires for Improved Responsivity and Detectivity of Photodetector. Issue 34 (16th July 2021) - Guo, Hang; Wang, Hongyue; Fan, Haibo; Ye, Qian; Zhang, Jin; Cao, Fengren; Li, Liang; Tong, Yu; Wang, Hongqiang
Abstract: Organic–inorganic hybrid MAPbI3 microwires show unique optoelectronic properties for high performances of photodetectors (PDs). However, the defects‐assisted nonradiative recombination is harmful for carrier transport, which limits the performances improvement of MAPbI3 microwires PDs. Traditional organic passivation agents effectively combine the surface defects of microwires and also reduce the mobility of overall film based on the perovskite microwires. Therefore, the improvement of internal carrier transport of microwires and the mobility of integrated film simultaneously is a particular challenge for fabrication of performances enhanced perovskite microwires PDs. Here, the Ti3 C2 T x NCs are fabricated by nonfocus laser irradiation in liquid environment, and hybrids the high conductive NCs in the MAPbI3 microwires. The presence of Ti3 C2 T x NCs renders defects passivation, enhancement of crystalline orientation, charge transport, and carrier extraction for MAPbI3 microwires, and boots the mobility of microwires based film, leading to about tenfolds enhancement of performances of PDs than that of the control. The maximum responsivity and the detectivity of the Ti3 C2 T x NCs embedded MAPbI3 microwires PDs reach to 1.70 A W −1 and 7.0 × 10 11 Jones in visible window, respectively. The findings suggest that the laser generated high conductive Ti3 C2 T x NCs is an effective additive for perovskite microwires to fabricate performances enhanced optoelectronics. Abstract : Ti3 C2 T x nanocrystals has been synthesized by using the technique of pulsed laser irradiation in liquid and composited into MAPbI3 microwires photodetectors. The presence of the nanocrystals improves the carrier transport of microwires, leading to the increased responsivity and detectivity of the photodetectors up to 1.70 A W −1 and 7.0 × 10 11 Jones, about tenfolds larger than that of control.